A simplified approach for single carrier visible light communication transceiver using off-the-shelf components - Ibhaze, Augustus; Orukpe, Patience; Edeko, Frederick (Department of Mechanical Engineering Universitas Muhammadiyah Surakarta, 2020)
Over the past decades, the demand for high-speed data transmission has grown exponentially, necessitating broadband technology integration to satisfy the emerging data-hungry society. This concern has engendered the proposition of a simplified optical wireless transceiver module using off-the-shelf electronic devices. According to the transistor to transistor logic levels, the transmitter module was made up of a single negative-positive-negative (NPN) transistor operated as a switch to drive an off-the-shelf 12V 5W light-emitting diode (LED). In contrast, the receiver was made up of a photodetector (solar) module for photons detection and back-conversion to electrical signals. The received signal was passed through a four-stage amplification process to remove the ambient noise and retrieve the data signal. The last transceiver module was demonstrated using personal computers. It was observed to perform at different optimum points consistent with exposure to fluorescent light, daytime, and night-time operations consequent upon the induced ambient light interference at data rates constrained by the communication device interface.